The effect of protease inhibitors on the cervical mucus of HIV-positive women taking norethindrone contraception. (April 2015) - Atrio, Jessica; Stek, Alice; Vora, Hita; Sanchez-Keeland, Lorraine; Zannat, Ferdous; Natavio, Melissa
Abstract: Objective To compare cervical mucus score (CMS) with and without protease inhibitors (PI) before and after taking norethindrone (NET). Study design This two-arm, researcher blinded, non-randomised, prospective study was conducted to evaluate cervical mucus quality in HIV-positive women taking progestin only pills. The study group was taking a PI, and compared to women taking ARV regimens that have demonstrated no significant interaction with NET in prior pharmacokinetic trials with combined oral contraceptives. The women had a cervical mucus score prior to NET administration. Mucus Scoring was repeated after 21 days of steady state exposure to oral NET 0.35 milligrams. Cervical mucus quality was quantified according to the World Health Organisation criteria, which include: volume, consistency, cellularity, spinnbarkeit, and ferning. Results Sixteen women took PI and 17 were controls. Baseline CMS were similar ( p ≥ 0.1). After 21 days CMS were similar among the two groups ( p = 1). Conclusions HIV-positive women taking PI demonstrated thickened cervical mucus with oral norethindrone 0.35 mg and are similar to HIV-positive women taking no PI therapy. This may suggest no difference in contraceptive efficacy of progestin only pills in HIV-positive women taking PI. Chinese Abstract 摘要 目的 比较服用炔诺酮（NET）前后，应用与不应用蛋白酶抑制剂（PI）宫颈粘液评分（CMS）情况。 实验设计 本实验为双向、单盲（研究者）、非随机、前瞻性研究。旨在评估HIV阳性妇女口服单孕激素丸避孕后宫颈粘液的质量。实验组采用蛋白酶抑制剂，对照组应用抗逆转录病毒疗法，两组在应用复方口服避孕药之前均通过药代动力学试验证实与炔诺酮无显著相互作用。受试者在服用炔诺酮前进行一次宫颈粘液评分。连续稳定口服炔诺酮0.35mg 21天后再分别记录粘液评分。根据世界卫生组织标准，宫颈粘液评分包括粘液量、粘稠度、细胞性、羊齿状结晶、拉丝度。 结果 16名女性采用蛋白酶抑制剂，17名为对照。宫颈粘液评分基线相似（ p ≥0.1）。21天后宫颈粘液评分也相似 (p =1)。 结论 接受蛋白酶抑制剂治疗的HIV阳性妇女与没有服用PI组口服炔诺酮0.35mg后，两者宫颈粘液稠厚程度相似。这可能表明应用蛋白酶抑制剂治疗的HIV阳性妇女口服炔诺酮的避孕效果无明显影响。